Solomon Islands : Health Financing Options - Somanathan, Aparnaa (World Bank, Washington, DC, 2013)
The objective of this Policy Note is to provide an assessment of available options for financing health care in the Solomon Islands. In doing so, the analysis will factor in the country-specific economic, social and political factors, which will ultimately influence the performance of the health financing mechanisms. The Note was motivated by the Solomon Islands Government s (SIG) interest in knowing whether financing options other than general revenue financing would be feasible and sustainable in the context of the Solomon Islands. In particular, SIG wished to consider whether Social Health Insurance presents a better alternative to General Revenue financing. The Note therefore seeks to provide the evidence and information needed to guide the Solomon Islands Government (SIG) in making decisions about different health financing options.